2016
DOI: 10.18178/ijesd.2016.7.7.826
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Phytoremediation and Bioremediation for Sandy Soil Contaminated with Petroleum Hydrocarbons

Abstract: Abstract-Soil contamination with petroleum hydrocarbons causes many problems for the surrounding environment. The current research aims at studying the performance of different in-situ remediation methods for the removal of total petroleum hydrocarbons (TPH) from sandy soil at different levels of contamination. The remediation methods that were tested include phytoremediation using alfalfa, bioremediation using Pseudomonase putida, and a combination. The soil was spiked with TPH at different levels (2.5%, 5.0%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…This confirms the results reported by numerous authors, who have indicated the negative impact of petrol on the activity of various enzymes, for example, dehydrogenases [8,9,27,28], phosphatases [27][28][29][30], catalase [9], β-glucosidase [28], peroxidases [9], urease [27,31], and nitrate reductase [32]. Oversaturation of soil with petrol considerably restricts the development or disturbs the survival of numerous soil microorganisms [33]. Borowik at al.…”
Section: Resultssupporting
confidence: 89%
“…This confirms the results reported by numerous authors, who have indicated the negative impact of petrol on the activity of various enzymes, for example, dehydrogenases [8,9,27,28], phosphatases [27][28][29][30], catalase [9], β-glucosidase [28], peroxidases [9], urease [27,31], and nitrate reductase [32]. Oversaturation of soil with petrol considerably restricts the development or disturbs the survival of numerous soil microorganisms [33]. Borowik at al.…”
Section: Resultssupporting
confidence: 89%
“…However, medium and especially high concentrations of petroleum products in soils inhibit the growth and development of alfalfa, as well as cause necrotic lesions of assimilation organs [Chekol, Vough, 2001;Gouda et al, 2016].…”
Section: Resultsmentioning
confidence: 99%
“…Higher reduction observed in stimulated phytoremediated treatments may be due to the addition of urea to crude oil polluted soil. The urea might have supplied growth limiting nutrient to the plant for metabolic activities thus enhancing (stimulating) the growth and phytoremediation potential of Chromolaena odorata in the polluted soil [38][39][40]. Shtangeeva et al [41] also report that the addition of urea to crude oil polluted soil enhanced the growth of wheat in such soil.…”
Section: Discussionmentioning
confidence: 99%